2021
DOI: 10.1017/s0007114521000039
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of provitamin A biofortified cassava to vitamin A intake in Nigerian pre-schoolchildren

Abstract: Background: Biofortified yellow cassava has been developed to alleviate vitamin A deficiency. We examined the potential contribution of yellow cassava to total Retinol Activity Equivalent (RAE) intake if replacing white by yellow cassava among pre-school Nigerian children. Methods: Dietary intake was assessed as part of a randomized controlled trial. Preschool children (n=176) were randomly assigned to receive either white cassava (WC) or yellow cassava (YC) for 17 weeks. Dietary intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Due to this, emphasis is being placed on the consumption of functional foods or "superfoods". Unfortunately, the conventional white-fleshed cassava is not rich in pro-vitamin A which is one of the target nutrients for addressing the double burden of malnutrition (Afolami et al 2021). Therefore, cassava has been biofortified through conventional cross-breeding.…”
Section: Overview Of Biofortified Cassava Food Production and Marketi...mentioning
confidence: 99%
“…Due to this, emphasis is being placed on the consumption of functional foods or "superfoods". Unfortunately, the conventional white-fleshed cassava is not rich in pro-vitamin A which is one of the target nutrients for addressing the double burden of malnutrition (Afolami et al 2021). Therefore, cassava has been biofortified through conventional cross-breeding.…”
Section: Overview Of Biofortified Cassava Food Production and Marketi...mentioning
confidence: 99%
“…[18][19][20][21] In terms of its impact on human health, VAC was found to contain enough vitamin A to contribute to improved nutritional status and reduce vitamin A deficiency 22,23 and efficacy studies conducted in Kenya with school-age children (5-13 years old) and in Nigeria with preschool children (3-5 years old) both showed that eating VAC increases children's vitamin A intake and status within 18 (Kenya) weeks of regular consumption. [24][25][26] Consumers' acceptance (liking) of food made with biofortified crops is another important prerequisite for the effectiveness of biofortification programs. To assess consumer acceptance of food made with VAC, a study conducted in rural areas of Oyo and Imo states of Nigeria found that regardless of the color of the commonly consumed local gari (cassava flour), consumers liked gari made with VAC varieties albeit in varying degrees depending on the color difference between local and VAC gari.…”
Section: Testing Biofortified Cropsmentioning
confidence: 99%
“…In terms of its impact on human health, VAC was found to contain enough vitamin A to contribute to improved nutritional status and reduce vitamin A deficiency 22,23 and efficacy studies conducted in Kenya with school-age children (5-13 years old) and in Nigeria with preschool children (3-5 years old) both showed that eating VAC increases children’s vitamin A intake and status within 18 (Kenya) weeks of regular consumption. 24 -26…”
Section: Testing Biofortified Cropsmentioning
confidence: 99%
“…Also, studies have reported increasing uptake and willingness to cultivate provitamin A cassava among farmers across the country, particularly women farmers (Oparinde et al, 2014;Effiong et al, 2015;Yusuf et al, 2020). In addition, efficacy studies conducted in Nigeria showed improvement in the vitamin A intake and the overall vitamin A status of children following consumption of provitamin A biofortified cassava (Onyeneke et al, 2020;Afolami et al, 2021a;Afolami et al, 2021b). Nevertheless, the recent Nigeria's National Food Consumption and Micronutrient Survey showed that only 3.20% of Nigerians consumed provitamin A cassava or any products made from it (FGN/IITA, 2022).…”
Section: Introductionmentioning
confidence: 99%